Bran from composite grain mixture as an object of deep processing. Part 2. Carbohydrate-amylase and lipid complexes - I. S. Vitol; E. P. Meleshkina; G. N. Pankratov (Пищевые системы, 2023)
Polycomponent bran obtained by joint grinding of a grain mixture from cereals (wheat), legumes (lentils) and oilseeds (flax) should be considered as a valuable secondary raw material, the use of which for deep processing will make it possible to obtain various food and feed ingredients. An assessment of the carbohydrate-amylase and lipid complexes of the three variants of multicomponent bran showed that the ratio of amylose and amylopectin in the starch of three-component bran is almost the same, however, in lentil-flax bran, the proportion of amylose is 1.6 times higher than in the first two variants. The specific activity of amylases in three-component bran is about 2 times higher than in lentil-flax bran. In addition, the latter are characterized by a higher content of reducing sugars and fiber. The molecular weight of amylases isolated from three-component bran, according to gel chromatography, was: α-amylase — 40,000 Da; β-amylase — 60,000 Da. It has been established that the addition of flax seeds to the grinding mixture significantly increases the fat content in bran 6.4; 6.0 and 12.9%. The fatty acid composition of the studied bristles is characterized by the predominance of unsaturated fatty acids. At the same time, the ratio of essential acids — linoleic acid (ɷ‑6) to α-linolenic acid (ɷ‑3) in favor of the most deficient α-linolenic acid — was typical for lentil-flax bran and amounted to 1:4.2. The activity of alkaline lipases, which exhibit their effect at pH 8.0 (mainly cereal lipases), and acid lipases (mainly oilseed lipases) with an optimum of action at pH 4.7 in three-component bran samples are approximately the same, and lentil-flax bran is characterized by a high specific acid lipase activity, which is approximately 4.2 times higher than the activity of acid lipases of three-component bran. The data obtained, along with data on the characteristics of the protein-proteinase complex of the studied types of bran, will be used in the development of methods for enzymatic modification (deep processing) and in the preparation of components for the creation of new food products with increased nutritional and biological value.